Improvement of RF-Pilot Based Phase Noise Compensation in CO-OFDM Communication Systems - Puntsri, Kidsanapong (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2015)
This paper presents an improvement of random phase noise (RPN) compensation under chromatic dispersion (CD) by a modified two stages RF-pilot-based. The first stage is similar to the conventional RF-pilot-based method and the second stage is called the fine RPN compensation. The second stage is used for minimizing the random rotation phasor by employing a RF-pilot window. The performance of RPN mitigation is evaluated by a numerical simulation method. At the forward error correction (FEC) limit, a sum laser linewidth tolerance of 3.1 MHz can be achieved for the 256-quadrature amplitude modulation (QAM) and 10 MHz for 64-QAM. For CD mitigation, the linear and cubic spline interpolation methods are investigated. The simulation results show that the cubic spline interpolation method provides a significant bit error rate performance improvement.